IMPLEMENTASI P5RA DALAM MENGEMBANGKAN KARAKTER SISWA KELAS X DI MADRASAH ALIYAH AL-ISLAM JAMSAREN SURAKARTA TAHUN PELAJARAN 2024/2025 - Syafadilla, Fahra Rifky; Sarjono, Joko; Praptiningsih, Praptiningsih (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to examine the implementation of the Project for Strengthening the Profile of Pancasila Students and Rahmatan Lil Alamin Students (P5RA) at Madrasah Aliyah Al-Islam Jamsaren Surakarta, including the supporting and inhibiting factors, as well as the outcomes of the program in developing students’ character. The research employed a qualitative method with a descriptive approach. Data were collected through documentation and interviews with the Vice Principal for Curriculum Affairs as the coordinator of P5RA implementation, an Akidah Akhlak teacher, and tenth-grade students. Data analysis was carried out through the stages of data collection, reduction, presentation, and conclusion drawing, while data validity was tested through triangulation. The findings show that the implementation of P5RA includes the planning stage (formation of a team, development of themes and project modules), implementation stage (one-week block-based activities with themes of entrepreneurship, local wisdom, and sustainable living), and evaluation stage (assessment through observation and rubrics). The program is supported by the school’s policy and teachers’ active roles but faces obstacles such as limited time, heavy academic workload, and the influence of social media.